Utilization of Zeolite as Tailing Reclamation Material of Gold mining - Suwardi, Suwardi; K., Kharisma Suzana (Jurnal Zeolit Indonesia, 2008)
Gold mining is one of the important mining in Indonesia, besides the mining of coal, nickel, copper, etc. Gold mining in Pongkor (PT Antam) applied deep mining system. Besides producing gold as the main product, mining activity also produces waste in the form of tailing obtained from its processing. Tailing is mining residue, whose gold and silver contents have been extracted, and the tailing has somewhat inferior chemical properties if returned to nature as planting media. Organic matter and zeolite are known as ameliorant which may be used as materials for improving physical and chemical properties of tailings. The objectives of this research were to study the effects of zeolite and compost application on the chemical properties of tailing, growth of sengon plants, and absorption of lead (Pb) by plants. Zeolite with the dosages of 0%, 10%, 20% and 30%; and compost with dosages of 0%, 10%, and 20% were added to tailings then used for planting seedling of sengon (Paraserianthes falcataria L. Nielsen). The results showed that tailing from gold mining of Pongkor had neutral pH values; high content of Ca and Pb; but very low CEC, organic-C, total- N, and bases other than Ca. Addition of zeolite and compost improve the chemical properties of tailing for growing plants. Zeolite had effect in increasing CEC, K and Ca; where as compost had effect in increasing all nutrient elements. Addition of zeolite and compost increased the height, diameter and crown width of sengon plants observed, although did not show significant effect (at Î± level of 5%), and was able to reduce Pb absorption in root and plant crown.